Colony Growth and Morphological Characterization of Sugarcane Root Bacteria and Sugarcane Field Exploration Bacteria in Fermented Liquid - Irawan, Triono Bambang; Kusuma, Indra Satria; Nuraisyah, Anni; Soelaksini, Liliek Dwi (Aspirasi Masyarakat Intelektual Islam Nusantara, 2024)
Rhizosphere bacteria play crucial roles in sugarcane fertility by providing nutrients, protecting against pathogens, and producing growth hormones. Exploring these bacteria can enhance sugarcane productivity through biofertilizers, biostimulants, and bioprotectants, reducing the need for costly inorganic fertilizers. This exploration is vital for optimizing sugarcane cultivation. The aims of the study were to determine the growth of bacterial colonies over 1, 2, and 3 weeks and to identify the morphology of sugarcane root bacteria and sugarcane exploratory bacteria growing in fermented liquid. The results showed: (i) Growth in the number of sugarcane root bacterial colonies was 7.7 × 10⁷ CFU/ml in week 1, increasing to 28.8 × 10⁷ CFU/ml in week 2, and further to 58 × 10⁷ CFU/ml in week 3 in fermented liquid. The growth of bacterial colonies exploratory of sugarcane land was 3.4 × 10⁷ CFU/ml in week 1, increasing to 19.7 × 10⁷ CFU/ml in week 2, and further to 62 × 10⁷ CFU/ml in week 3 in fermented liquid; (ii) Morphology of sugarcane root bacterial colonies from week 1 to week 3 included colony colors: yellow, pink, blue, milky white, blue center; colony sizes: pinpoint, medium, large; colony shapes: circular, irregular; elevation: convex, flat; surface textures: smooth, mucoid; edges: regular, irregular. Bacterial cell shape was bacilli and Gram-positive; and (iii) The morphology of bacterial colonies from sugarcane field exploration from week 1 to week 3 included colony colors: yellow, pink, blue, milky white, blue center; colony sizes: small, medium, large, pinpoint; colony shapes: circular, irregular; elevation: convex, flat, umbonate, raised; surface textures: smooth, mucoid; edges: regular, irregular.